Lanskap Penggunaan Media Sosial di Kota Batam: Pendekatan Pemetaan Kuantitatif - Angel Purwanti; Angeline Wong (LPPM Universitas Putera Batam, 2025)
This study aims to map the pattern of social media use in Batam City with a descriptive quantitative approach based on PSPP. A total of 384 respondents were selected through random sampling techniques, representing various age groups, genders, education, and location. The results show that Instagram and TikTok are the dominant platforms among young users, especially women, while Facebook and YouTube are more widely used by men. The Chi-Square test confirmed a significant relationship between gender and social media platform preferences (χ² = 29.45; p < 0.001). Analysis of social media usage dimensions—context, communication, collaboration, and connection—shows that engaging, polite, and interactive content is preferred over incentive-based promotions. These findings strengthen the relevance of Social Digital Literacy theory and Agenda Setting, as well as provide empirical contributions to the development of public communication strategies, community digital literacy, and demographic-based social media policies in Batam City